Identification of a microRNA encoded by Anticarsia gemmatalis multiple nucleopolyhedrovirus. (August 2020) - Ferrelli, María Leticia; García, María Laura; Romanowski, Víctor; Reyes, Carina Andrea
Graphical abstract: Highlights: In silico prediction of agmnpv-miR-4 was performed based on homology to bmnpv-mir-4 . agmnpv-miR-4 was detected by northern blot in AgMNPV-infected High five cells. agmnpv-miR-4 precursor was detected in AgMNPV-infected A. gemmatalis larvae. Homologs to agmnpv-mir-4 were found in baculoviruses closely related to AgMNPV. Abstract: MicroRNAs are regulatory RNAs that are scarcely described in Baculoviruses. In this work we predicted a microRNA in silico, denominated agmnpv-miR-4, encoded in the genome of Anticarsia gemmatalis Nucleopolyhedrovirus (AgMNPV), which is homologous to the already validated bmnpv-miR-4 from Bombyx mori Nucleopolyhedrovirus (BmNPV). Considering information known for bmnpv-miR-4 such as seed sequence, coding location in the genome and putative target binding, we searched for the coding sequence of agmnpv-miR-4 in AgMNPV genome. A precursor sequence of agmnpv-miR-4 was predicted, and we identified a putative 23 nt mature microRNA, agmnpv-miR-4, coded in the complementary strand of AgMNPV-2D between positions 49, 450 and 49, 472. We validated agmnpv-miR-4 by Northern blot from HighFive cells and A. gemmatalis larve extracts infected with AgMNPV.